Facets of fieldwork: essays in honor of Jürg Wassmann - Poser, Alexis Themo von; Poser, Anita von (Heidelberg studies in Pacific anthropology, 2017)
Taim Bipo: the quest for the past by the members of the Basel Sepik Expedition 1972-74 / Markus Schindlbeck -- Thinking along the same lines: varieties of initiation and varieties of fieldwork in Sepik and Madang / Patrick F. Gesch -- The coral gardens are losing their magic: the social and cultural impact of climate change and overpopulation for the Trobriand Islanders / Gunter Senft -- Group dialogues, videos and multilocality in researching rituals / Antje Denner -- "I didn't know that there were other worlds out there": inside a multi-sited ethnography / Stephanie Walda-Madel -- "Houses jumbles everywhere"?: visions of a "village" in Papua New Guinea / Anita von Poser -- The chase for archival material and biographical information in the "field" of archives: remvarks about a research project, carried out in Chile, Rapanui and other places / Hermann Mückler -- References to time and space in Melanesian Music / Raymond Ammann -- The early field and commercial recordings of Kuman music: research using repatriated music in Papua New Guinea, and recent threats to cultural diversity / Don Niles and Edwar Gende -- Foreign confidants: a field day narrative / Angella Meinerzag -- Endangered fields: experiencing anthropological research in Iran / Shahnaz R. Nadjmabadi -- Exchanging anthropological knowledge: a university partnership program between Madang and Heidelberg / Verena Keck -- The restitution of a carving pattern to Kayan, Papua New Guinea / Alexis Th. von Poser -- Challenges and profits of interdiscliplinary fieldwork in linguistic and cognitive anthropology / Svenja Völkel -- The trouble of having a psychologist sharing fieldwork / Pierre R. Dasen -- "Just plain folks": anthropology meets psychology / Joachim Funke
Keywords: Wassmann, Jürg; Wassmann, Jürg -- 1946-; Aufsatzsammlung; Festschrift; Feldforschung; Ethnologie